Callitrichine gammaherpesvirus 3 and Human alphaherpesvirus 1 in New World Primate negative for yellow fever virus in Rio de Janeiro, Brazil - Flávia Freitas de Oliveira Bonfim; Maria Angélica Monteiro de Mello Mares-Guia; Marco Aurélio Horta; Marcia Chame; Amanda de Oliveira Lopes; Rafael Santos; Carlos Alexandre Rey Matias; Marcelo Alves Pinto; Ana Maria Bispo de Filippis; Vanessa Salete de Paula (Memorias do Instituto Oswaldo Cruz, 2022)
BACKGROUND Herpesvirus transmission between humans and non-human primate (NHP) can occur through contact scratches with lesions, infected saliva, and mainly through contaminated food. Therefore, cross-infection can lead to severe illness or even death for both the animal and human. In 2017, during the yellow fever (YF) outbreak in Brazil, species of the New World Primates (NWP) from Rio de Janeiro state, tested negative for yellow fever virus (YFV) detection. OBJECTIVES To evaluate herpesvirus in the population NWP in Rio de Janeiro. METHODS To investigate, liver samples of 283 NWP, from several regions of the state of Rio de Janeiro, were tested for the herpesvirus family using a Pan-polymerase chain reaction (Pan-PCR) and sequencing. FINDINGS 34.6% (98/283) tested positive for at least one herpesvirus; 29.3% (83/283) tested positive to Human alphaherpesvirus 1 (HSV-1), this virus from humans can be lethal to New World monkey; 13% (37/283) were detected Callitrichine gammaherpesvirus 3 (CalHV-3), responsible for lymphoproliferative disease that can be fatal in NWP. In addition, CalHV-3 / HSV-1 co-infection was in 11.6% (33/283) of the samples. MAIN CONCLUSIONS Pan-herpesvirus was useful to identify species-specific herpesviruses and virus from human that can infect animals. Furthermore, during an outbreak of YF other infections should be monitored.